SYSTEMATIC LITERATURE REVIEW: THE ROLE OF ENTREPRENEURSHIP EDUCATION IN ENHANCING ENTREPRENEURIAL INTEREST - Shahrul Dwi Ananta; Khoirul Ilmiati; Sudarmiatin; Mokhammad Nurruddin Zanky (Jurnal Penelitian Progresif, 2026)
This study aims to analyze the effectiveness of entrepreneurship education in enhancing the entrepreneurial interest of Vocational High School (SMK) students using a Systematic Literature Review (SLR) approach. Data were collected from nationally accredited journals indexed in Sinta 1 and Sinta 2, namely the Journal of Education and Learning (EduLearn) and the Jurnal Ekonomi Pendidikan dan Kewirausahaan, covering publications from 2020 to 2025. From the literature search and screening process, 15 relevant articles were identified, of which 5 met the inclusion criteria for further analysis. The synthesis results indicate that entrepreneurship education has a positive and significant effect on increasing the entrepreneurial interest of SMK students. The effectiveness of this program is further enhanced when supported by family environment, creativity, community involvement, and a conducive learning atmosphere. However, entrepreneurial knowledge alone is not sufficiently effective without reinforcement of psychological and social aspects, such as entrepreneurial spirit and family support. Therefore, a holistic, integrative, and experience-based model of entrepreneurship education is recommended as the most effective approach to foster entrepreneurial interest among vocational high school students.